Response of cassava to water stress - El-Sharkawy, Mabrouk A.; Cock, James H. (Springer, 1987)
Cassava (Manihot esculenta Crantz) is a staple food for a large sector of human population in the tropics. It is widely produced for its starchy roots by small farmers over a range of environments on poor infertile soils with virtually no inputs. It is highly productive under favorable conditions and produces reasonably well under adverse conditions where other crops fail. The crop, once established, cansurvive for several months without rain. There is a wide variation within the cassava germplasm for tolerance to prolonged drought and the possibility to breed and select for stable and relative high yields under favorable and adverse conditions does indeed exist. Research with several cassava clones at CIAT has shown that high root yield under mid term stress is not incompatible with high yield under nonstress conditions. Plant types with high yield potential under both conditions (e.g. the hybrid CM 507-37) are characterized by having slightly higher than optimum leaf area index under nonstress conditions, higher leaf area ratio and more intensive and extensive fine root system.